ISLAM AND FEMINISM THEOLOGY - Muhaemin Latif (Universitas Islam Negeri Alauddin Makassar, 2018)
This article examines the relationship between Islam and feminism theology. Both Islam and feminism are strongly important to be discussed in the field of Islamic discipline, especially the issue of women liberation. As can be seen in the classical theology, the issue of feminism is not the main concern among the Muslim Intelectuals. Some argue that Islam do not take into account the liberation of women, they even think that Islam assume women as the “second creature”. In addition, the creature as well as the perfection of women is extremely depend on the existence of men. This research aims at answering these assumptions. The research suggests that feminism are the foundations of Islamic teaching. Historically, the emergence of Islam in Arab peninsula illustrates the women liberation from the Arabic doctrine and tight tradition. This article believea that the positioning of women in line with men was influenced by the fallacies of interpretation toward Koran and prophet tradition. A number of quranic excegeses are genderly biased. So, this research proves that liberating women from dogmatic tradition is rethinking the products of interpretation either in the Koran or prophet tradition.